Diana outside the City (Archaeologia Adriatica, 2008)
The article discusses the well-known relief from Čitluk, which was engraved into a cliff face near the city gates of the Roman Aequum. Today it is in the Archaeological Collection of the Franciscan Museum in Sinj. The place where the relief was located is indicative: near the city gates, but outside the city, a place that rightfully belongs to Diana and Silvanus in the Roman tradition – as the protectors of borders and boundaries. Diana and Silvanus occupy the same place on the triumphal arch of Trajan in Benevento. On the other side, Silvanus is depicted completely according to local iconography, which was taken over from the Greek Pan, and accordingly this pair can be considred local. Diana and Silvanus are gods who belong to wild, uncultivated landscapes, the world of the “other” and “different”, the world that in Hodder’s terminology was called agrios, in contrast to the fenced, domestic, known world, which in the same terminology was called domus.
Keywords: Diana; Čitluk; Aequum; Roman religion; Benevento